1984
DOI: 10.3109/00016358408993863
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms of mandibular dysfunction after introduction of experimental balancing-side interferences

Abstract: A double-blind study was performed in two groups of young, healthy women without signs or symptoms of mandibular dysfunction. Each group contained 12 individuals. In one of the groups, balancing-side interferences were applied bilaterally, whereas the application was simulated in the other group. The participants were re-examined after 2 weeks. Ten individuals in the experimental group reported one or more subjective symptoms during the 2 weeks, whereas seven exhibited clinical signs of dysfunction. The common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2
7

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 10 publications
1
17
2
7
Order By: Relevance
“…In subjects with no TMD history and true interferences, adaptation to these symptom dimensions seemed to occur over time. The results are much in line with those of Magnusson & Enbom [19], who also found that difficulties in chewing were indicative at the beginning, but the symptoms diminished after a few days indicating an adaptation to the new situation. However, in the present study, chewing problems persisted throughout the 2-week observation period in the subjects with TMD history and true interferences.…”
Section: Discussionsupporting
confidence: 90%
“…In subjects with no TMD history and true interferences, adaptation to these symptom dimensions seemed to occur over time. The results are much in line with those of Magnusson & Enbom [19], who also found that difficulties in chewing were indicative at the beginning, but the symptoms diminished after a few days indicating an adaptation to the new situation. However, in the present study, chewing problems persisted throughout the 2-week observation period in the subjects with TMD history and true interferences.…”
Section: Discussionsupporting
confidence: 90%
“…Among epidemiological studies, some authors reported a positive correlation between mediotrusive side interference and signs and symptoms of functional disturbance [7,12]. In this research, we especially focused on the occlusal contact patterns during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The effects on jaw function of introducing interferences in the occlusion have clearly been demonstrated (4)(5)(6). Kampe (7) has claimed that dental restorations are responsible for the development of signs and symptoms of mandibular dysfunction.…”
mentioning
confidence: 98%